2021
DOI: 10.1002/uog.23641
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of early miscarriage and client satisfaction with treatment: comparison between expectant management and misoprostol treatment in a randomized controlled trial

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has also been used to determine the relationships among perinatal grief and factors such as number of pregnancy losses, gestational age at time of loss, religiosity, ruminative thoughts, posttraumatic symptoms, and posttraumatic growth (Cowchock et al, 2010(Cowchock et al, , 2011Gozuyesil et al, 2021;Krosch & Shakespeare-Finch, 2017;Ozgen et al, 2022;Purandare et al, 2012;Penelo et al, 2017). In experimental studies, the PGS has been used to assess the effectiveness of clinical interventions (Fernlund et al, 2021;Johnson & Langford, 2015). The PGS has been translated to Spanish, Turkish, Arabic, Chinese, Persian, Italian, and Greek (Al-Maharma et al, 2016;Capitulo et al, 2010;Könes et al, 2017;Lai et al, 2013;Maniatelli et al, 2018;Ravaldi et al, 2020;Siadatnezhad et al, 2018;Yan et al, 2010), has demonstrated good reliability and validity in all translations, and has been widely used internationally.…”
Section: Meta-analysis Of Pgs -Short Form (Svpgs)mentioning
confidence: 99%
“…It has also been used to determine the relationships among perinatal grief and factors such as number of pregnancy losses, gestational age at time of loss, religiosity, ruminative thoughts, posttraumatic symptoms, and posttraumatic growth (Cowchock et al, 2010(Cowchock et al, , 2011Gozuyesil et al, 2021;Krosch & Shakespeare-Finch, 2017;Ozgen et al, 2022;Purandare et al, 2012;Penelo et al, 2017). In experimental studies, the PGS has been used to assess the effectiveness of clinical interventions (Fernlund et al, 2021;Johnson & Langford, 2015). The PGS has been translated to Spanish, Turkish, Arabic, Chinese, Persian, Italian, and Greek (Al-Maharma et al, 2016;Capitulo et al, 2010;Könes et al, 2017;Lai et al, 2013;Maniatelli et al, 2018;Ravaldi et al, 2020;Siadatnezhad et al, 2018;Yan et al, 2010), has demonstrated good reliability and validity in all translations, and has been widely used internationally.…”
Section: Meta-analysis Of Pgs -Short Form (Svpgs)mentioning
confidence: 99%
“…We recently conducted and published a randomized controlled trial designed to compare expectant management with misoprostol treatment in early (before 13 weeks) miscarriage with a retained gestational sac in the uterus 3,17 . The primary aim of the trial was to compare treatment success between the two management strategies.…”
Section: Introductionmentioning
confidence: 99%